Factors Associated with the Prevalence of Elective Non-Surgical Management - Mujtaba M. Al khamees, Mohammed A. Al ali, Abdullah M. Al Buali, Ahmed M. Al Buali, Loai S. Albinsaad, Mohammed Alessa (South Eastern European Journal of Public Health, 2025)
Surgical interventions are widely regarded as the primary treatment option for various medical conditions. However, a considerable number of patients looking for elective non-surgical management (ENSM), which can significantly influence patient outcomes depending on the nature of the condition. The decision-making process regarding ENSM is influenced by numerous factors currently under investigation. This study aimed to explore the factors associated with ENSM among patients in Saudi Arabia. A validated questionnaire, developed and endorsed by field and linguistic experts, was disseminated via social media to ensure random distribution. A total of 375 participants meeting inclusion and exclusion criteria were enrolled, with a gender distribution of 66.1% male and 33.9% female. Among the participants, 13.9% had undergone surgical procedures. Key concerns contributing to the preference for ENSM included inadequate information provided by doctors (30.7%), lack of discussions on alternative treatment options (45.6%), cultural reluctance toward seeking second opinions (37.6%), and apprehension about recovery (44%). These findings underscore the complex interplay of medical, informational, cultural, and emotional factors influencing patients' decisions regarding surgical and non-surgical treatment options. Understanding these factors is crucial for improving patient-centered care and enhancing decision-making processes in clinical practice.